1999
DOI: 10.1177/002215549904700406
|View full text |Cite
|
Sign up to set email alerts
|

Keratan Sulfate Glycosaminoglycans in Murine Eosinophil-specific Granules

Abstract: SUMMARYWe examined the presence of sialyl glycoconjugates in specific granules from murine bone marrow eosinophils. Lectin cytochemistry using Maackia amurensis lectin II (MAL II) specific for sialyl ␣-2,3 galactose residues demonstrated positive labeling in both immature and mature specific granules. Pretreatment with Clostridium neuraminidase or keratanase II eliminated the positive labeling of MAL II in the specific granules. High iron diamine-thiocarbohydrazide-silver proteinate physical development (HID-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In addition, basophils and mucosal mast cells [46] have been shown to contain the disaccharide 2-O-sulphated IdoA-4-O-sulphated GalNAc (CS-diB), as shown in Table 1. The presence of both intracellular keratan sulphate [47] and hyaluronan [18,21] has also been documented.…”
Section: Gag Structuresmentioning
confidence: 95%
“…In addition, basophils and mucosal mast cells [46] have been shown to contain the disaccharide 2-O-sulphated IdoA-4-O-sulphated GalNAc (CS-diB), as shown in Table 1. The presence of both intracellular keratan sulphate [47] and hyaluronan [18,21] has also been documented.…”
Section: Gag Structuresmentioning
confidence: 95%
“…Keratanase cleaves the internal β1–4 galactosidic linkages in KS and generally affords oligosaccharides. In contrast, keratanase II cleaves β1–3 glucosaminidic linkages to galactose, as well as those in KS to galactose-6-sulfate, releasing monosulfated or disulfated disaccharides from KS [11]. …”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we demonstrated that sialyl residues detected by MAL II are expressed as terminal sugar residues of keratan sulfate proteoglycan [5], which are the sole proteoglycan-containing sialic acids [8]. A biochemical study demonstrated that GAGs may form complexes with lysosomal enzymes, inactivating their enzyme activities [9, 10].…”
Section: Resultsmentioning
confidence: 99%
“…Studies using various staining methods have demonstrated that the acidic substances are sulfated [3, 4]and sialyl glycoconjugates [5]. Sulfated residues were labeled by high iron diamine-thiocarbohydrazide-silver proteinate-physical development (HID-TCH-SP-PD) staining [6].…”
Section: Introductionmentioning
confidence: 99%